Synthesis, Structure, and Electrical Property of Ce1−xSr1+xGa3O7−δ - Xiaohui Li; Jungu Xu; Junshu Xiaofeng; Xiaojun Kuang (Advances in Materials Science and Engineering)
Ce1−xSr1+xGa3O7−δ powders were synthesized by a solid state reaction method under reducing atmosphere. Single melilite phase was obtained for x≤0.2. X-ray diffraction pattern displays a preferred orientation on (002) peak of the Ce0.9Sr1.1Ga3O7−δ composition. Scanning electron microscope disclosed the nanoscale needle-like micromorphology of this material, with an average length of ~2.5 μm and a diameter of ~500 nm. Transmission electron microscopy and selected area electron diffraction reveal the single crystal nature of these individual Ce0.9Sr1.1Ga3O7−δ needles and build up a relationship between the preferred orientation observed in X-ray diffraction pattern and the micromorphology. The phase stability of Ce1−xSr1+xGa3O7−δ in air was studied and the electrical property was investigated by impedance spectroscopy.